Indeks Subjek Volume 29, Tahun 2009 - Indeks Subjek Volume 29, Tahun 2009 (agriTECH, 2009)
Aerobasidium pullulans 64Agroindustrial security 209Antioxidant 10, 29Antioxidant activity 16, 130Artificial Neural Network 219Assessment 198Biocatalyst 122Broiler chicken 142Carbonyls content 59Carrot frying 147Cashew 189Cassava bagasse 53Cellulase 53Characterization 1Chicken muscle 79Cholesterol 29Coconut 137Coffee 189Concentrate 108Cream 137Crystallization 177Curcumin 130Decision making system 152Deep fat vacuum frying 147Deep frying 96Depository efficiency of cation 36Design 42Determination 183Dried fruit slices 16Dry fractionation 117DSC 117DSC and rheometry 177